Optical Coherence Tomography Angiography Characteristics of Polypoidal Lesions in Caucasians - Daniel Ahmed-Balestra; Alexandra Graf; Martin Stattin; Anna-Maria Haas; Stefan Kickinger; Michael Jacob; Claus Zehetner; Katharina Krepler; Siamak Ansari-Shahrezaei (Journal of Ophthalmology)
Purpose. The aim of the study is to analyze the swept source-optical coherence tomography angiography (SS-OCTA) characteristics of polypoidal lesions in Caucasian patients. Methods. In this retrospective observational case series, 43 polypoidal lesions in 32 eyes of 32 patients were diagnosed using indocyanine green angiography (ICGA) and compared to SS-OCTA at a tertiary medical retina center (Clinic Landstraße, Vienna Healthcare Group, Austria) between June 2017 and March 2020. Vascularity was identified by color-coded B-scan SS-OCTA while morphology was described as revealed by en face SS-OCTA after alignment with ICGA-confirmed findings. Results. In total, SS-OCTA detected all polypoidal lesions, as identified by ICGA. On B-scan SS-OCTA, circumscribed flow was detected in 33 (76.7%) polypoidal lesions and diffuse flow in 10 (23.3%) lesions. On en face SS-OCTA, polypoidal lesions appeared morphologically as 19 tangled vessel balls (44.2%), 6 tangled vessel balls next to dilated vessels (13.9%), 8 vascular dilatations (18.6%), and 8 ill-defined vascular networks (18.6%), leaving 2 lesions (4.6%) undetected. Circumscribed flow was significantly associated with tangled vessel balls (p=0.005). Conclusion. This study highlights the importance of a multimodal imaging approach, including SS-OCTA, for the evaluation of polypoidal lesions. Our findings suggest a morphological heterogeneity of vascular patterns in Caucasian patients with polypoidal lesions, as pictured by SS-OCTA.